Impact of flooding on health-related quality of life in England: results from the National Study of Flooding and Health. (30th March 2020) - Robin, Charlotte; Beck, Charles; Armstrong, Ben; Waite, Thomas David; Rubin, G James; ,; Oliver, Isabel
Abstract: Background: Flooding can have extensive effects on the health and wellbeing of affected communities. The impact of flooding on psychological morbidity has been established; however, the wider impacts of flooding exposure, including on health-related quality of life (HRQoL), have not been described. Methods: Using data from the English National Study of Flooding and Health cohort, HRQoL 2 and 3 years post-flooding was assessed with the EuroQol Group EQ-5D-5L tool. Associations between exposure groups (flooding and disruption from flooding) and HRQoL were assessed, using ordinal and linear regression, adjusting for a priori confounders. Results: For both 2 and 3 years post-flooding, the median HRQoL scores were lower in the flooded and disrupted groups, compared with unaffected respondents. A higher proportion of flooded and disrupted respondents reported HRQoL problems in most dimensions of the EQ-5D-5L, compared with unaffected respondents. In year 2, independent associations between exposure to flooding and experiencing anxiety/depression [adjusted odds ratio (aOR) 7.7; 95% CI 4.6–13.5], problems with usual activities (aOR 5.3; 95% CI 2.5–11.9) and pain/discomfort (aOR 2.4; 95% CI 1.5–3.9) were identified. These problems persisted 3 years post-flooding; associations between exposure to flooding and experiencing anxiety/depression (aOR 4.3; 95% CI 2.5–7.7), problems with usual activities (aOR 2.9; 95% CI 1.5–6.1) and pain/discomfort (aOR 2.5; 95% CI 1.5–4.2) were identified. Conclusions: Exposure to flooding and disruption from flooding significantly reduces HRQoL. These findings extend our knowledge of the impacts of flooding on health, with implications for multi-agency emergency response and recovery plans.